Synthesis, characterization and antibacterial screening of 3-hydroxy-2-[3-(2/3/4-methoxybenzoyl) thioureido] butyric acid - Mohd Yusof, Mohd Sukeri; Ramli, R.; Che Soh, Siti Kamilah; Ngah, Nurziana (World Academy of Science, Engineering and Technology, 2019)
This study presents the synthesis of a series of methoxybenzoylthiourea amino acid derivatives. The compounds were obtained from the reactions between 2/3/4-methoxybenzoyl isothiocyanate with threonine. All of the compounds were characterized via mass spectrometry, 1H and 13C NMR spectrometry, UV-Vis spectrophotometer and FT-IR spectroscopy. Mass spectra for all of the compounds showed the presence of molecular ion [M]+ peaks at m/z 312, which are in agreement to the calculated molecular weight. For 1H NMR spectra, the presence of OCH3, C=S-NH and C=O-NH protons were observed within the range of δH 3.8-4.0 ppm, 11.1-11.5 ppm and 10.0-11.5 ppm, respectively. 13C NMR spectra in all compounds displayed the presence of OCH3, C=O-NH, C=O-OH and C=S carbon resonances within range of δC 55.0-57.0 ppm, 165.0- 168.0 ppm, 170.0-171.0 ppm and 180.0-182.0 ppm, respectively. In UV spectra, two absorption bands have been observed and both were assigned to the n-π* and π-π* transitions. Six vibrational modes of v(N-H), v(O-H), v(C=O-OH), v(C=O-NH), v(C=C) aromatic and v(C=S) appeared in the FT-IR spectra within the range of 3241-3467 cm-1, 2976-3302 cm-1, 1720-1768 cm-1, 1655-1672 cm-1, 1519-1525 cm-1 and 754-763 cm-1, respectively. The antibacterial activity for all of the compounds was screened against Staphylococcus aureus, Staphylococcus epidermidis, Salmonella typhimurium and Escherichia coli. However, no activity was observed.